State-Owned Or State-Owed? Evaluating Indonesia'S Divestment Returns From Pt Vale Indonesia Tbk - Daulay, Anggi Anugerah; Qadri, Resi Ariyasa (Pusat P2M Politeknik Negeri Batam, 2024)
This study endeavors to predict and elucidate the prospective returns on governmental investments in the divestment shares of PT Vale Indonesia Tbk. Financial data were collated through the documentation technique, leveraging annual reports from the company. The financial information was subsequently analyzed employing a quantitative methodology